Pemanfaatan Potensi Limbah Bahan Alam Sebagai Zat Aktif Sediaan Body Scrub - Indah Sari Amanatun Nisa; Janwar Janwar; Melani Anggraeni; Nia Yuniarsih (Syntax Corporation Indonesia, 2022)
Skin is the outermost part of the body and is in direct contact with the environment, sun exposure and climate change make our skin dull, wilted, and wrinkled. Intensive care is needed by the skin to prevent damage to the skin. Therefore, a Body Scrub serves to lift the skin of the body that is rough and dull. Scrub also functions to help accelerate the turnover of new body skin cells, which are healthier and cleaner. Skin that was rough and dull will look bright and not dull anymore. The skin will feel smooth, soft, not easily dry. In this review, we will discuss traditional waste-based Scrubs that are good for the skin. The data search was carried out by reviewing the literature which includes data review, collection of related research results that have been published using Google Scholar and Pubmed. Some plant wastes that can be used as Body Scrub preparations include onion skin (Allium Cepa L) containing chemical compounds that have the potential as antioxidants, namely flavonoids, coffee grounds and temulawak rhizomes (Curcuma Xanthorrhiza Roxb) containing chemical compounds that have the potential as antioxidants, namely flavonoids and polyphenols. Coconut fiber and charcoal (Cocos Nucifera) Contains chemical compounds that have the potential as antioxidants, namely tanis, lime peel (Citrus aurantiifolia) contains chemical compounds that have antibacterial potential, namely triterpenoids, and rice husks (Oriza Satyva) contain activated carbon that can function as antioxidants. The results obtained from the five wastes can be used as Body Scrub preparations.